PENGETAHUAN DAN PERILAKU PERAWATAN KAKI PADA PENDERITA DIABETES MELITUS TIPE 2 DI PUSKESMAS GONDANG SRAGEN - Hesti Septia Ningrum; Ida Imamah (Journal Keperawatan, 2022)
Type II Diabetes Mellitus due to a decrease in sensitivity to insulin (insulin resistance) or due to a decrease in the amount of insulin produced. Complications of patients with type II diabetes mellitus include diabetic foot ulcers, where diabetic ulcers can be done by doing good foot care. The purpose of this study was to describe the knowledge and behavior of foot care in patients with type II diabetes mellitus at the Gondang Health Center. The research method uses descriptive quantitative. Sampling using purposive sampling technique, with a total sample of 57 respondents. The research instrument used a Diabetic Foot Knowledge Scale (DFKS) foot care knowledge questionnaire and a Nottingham Assessment of Functional Footcare (NAFF) foot care behavior questionnaire. The analysis used is univariate analysis with frequency distribution. The results of the univariate test showed that with type II Diabetes Mellitus 37 respondents (64.9%) had poor knowledge, 41 respondents (71.9%) had poor behavior. The conclusion of the study was that the majority of respondents had poor foot care knowledge and behavior due to lack of information about diabetic foot care.